Case report: Autosomal recessive bestrophinopathy with macular cysts and MNV over 13-year follow-up - Zhang, Lei; Wang, Hai-Yan; Jia, Wei; Wang, Ru; Wang, Yu-Sheng; Cui, Yang-Yang (Frontiers in Genetics, 2022)
Purpose: To describe the phenotype and genotype of a patient with autosomal recessive bestrophinopathy (ARB) over a 13 year of follow-up period. Methods: The phenotype of the subject was described after a complete ophthalmological examination including fundus photography, optical coherence tomography (OCT), fundus autofluorescence, fluorescein angiography (FA), indocyanine green angiography (ICGA), electrooculography (EOG), electroretinography (ERG), and multifocal electroretinogram (mfERG). Genetic analyses were carried out by screening the variations via whole-exome sequencing. Results: This patient presented with retinoschisis and cystic changes when he was 7 and diagnosed as X-linked retinoschisis. At 13th-year after first presentation, enlarged macular cysts with retinoschisis, macular neovascularization (MNV) and subretinal fluid were displayed on OCT. Autofluorescence showed hyperfluorescence corresponding to the area of RPE change. EOG showed no light peak, and Arden ratio was less than 2.0. Whole-exome sequencing revealed that the compound heterozygous sequence variations (p. [Arg47Leu; Trp287*]) in the coding sequence of BEST1 allele inherited from his parents respectively. Thus, diagnosis of ARB combined with secondary MNV was made. Conclusions: Patients with compound heterozygous Best1 mutations developed ARB, which could show significant retinoschisis at the young age. Genetic analyses, autofluorescence and EOG are essential to diagnose ARB correctly in consequence of considerable phenotypic variations.